Emerging role of junctophilin-2 as a regulator of calcium handling in the heart - Garbino Alejandro; Wehrens Xander HT (Acta Pharmacologica Sinica, 2016)
Junctophilin-2 (JPH2) is a membrane-binding protein that plays a key role in the organization of the junctional membrane complex (JMC) in cardiac myocytes. JPH2 is believed to keep the plasma membrane and sarcoplasmic reticulum at a fixed distance within the JMC, which is essential for proper Ca2+-induced Ca2+ release during the excitation-contraction process. Recent studies have revealed that mutations in the JPH2 gene are associated with hypertrophic cardiomyopathy, highlighting the importance of this protein for normal cardiac physiology. In this paper, we review current knowledge about the structure and function of junctophilin-2 in the heart.